Multidimensionality and the Validity of Deliberation (2020)
Many deliberation problems are multidimensional: the arguments for and against the proposed solutions appeal to values that belong to different dimensions. Thus, for instance, the arguments in favor of the proposal to negotiate to solve the problem of a domestic armed conflict may draw upon peace, whereas the arguments against it may invoke justice. This enables spokespeople to accept the premises of an argument without committing themselves to agreeing to its conclusion and justifying such an argument by emphasizing the premises of the opposing argument. “Yes, a negotiation would reduce the number of deaths caused by political violence, but it would also lead to impunity; therefore, we should not negotiate.” If this situation were indomitable, the deliberation arguments could never be valid; they could never be such to the extent that the acceptance of the premises would force whoever accepts them to agree to the conclusions. In this paper, some of the answers to this problem are considered: the answers of Kock (2009), Govier (2010), and Olmos (2016) as well as the response of Macagno and Walton (2018). Furthermore, several issues found in these answers are pointed out, and in an attempt to provide a solution, a distinction is made between the cases wherein it is possible and those wherein it is impossible to overcome the problem of deliberation multidimensionality.